AN INTEGRATED APPROACH TO LOGISTIC RISK ASSESSMENT (Economic journal of Lesya Ukrainka Volyn National University, 2021)
The article considers theoretical and methodological aspects of logistics, namely logistics processes, logistics chain, logistics system, logistics management, logistics risk. A method of logistics management as an integrated process using the so-called network planning is proposed. This method allows a systematic approach to planning and managing the process of developing a new complex system. The process itself is seen as a single, inseparable process of interdependent operations aimed at achieving the ultimate goal. When analyzing the network model, a quantitative assessment of the time and cost of work performed. Elements of risk management in the logistics of enterprises using qualitative and quantitative analysis are considered.
Keywords: logistics, risk, critical path method (CPM), program evaluation and review technique (PERT), logistics chain, critical activity, network planning, qualitative and quantitative risk assessment.